Gait Analysis for Walking on Flat Footwear and High Heels - Jia Yi Soh; Muhammad Asyraf Danial Azahari; Nai Chuan Yek; Muhammad Asri Abu Bakar; Harith Aiman Suhaimi; Mahdzir Jamiaan; Chin Fhong Soon (Emerging Advances in Integrated Technology, 2025)
Gait analysis has transformed traditional methods of studying human locomotion by enabling precise monitoring and real-time analysis of critical biomechanical parameters. The purpose of this project is to design a portable gait analysis system as a prototype to evaluate the effects of different footwear on walking dynamics. The acceleration sensor was implemented into a wearable device to collect data and analyze gait variations between walking in flat footwear and high heels. The system monitors angular velocity, acceleration, and an-gles across three axes (x, y, and z). Key features of this system in-clude its ability to record motion data in real time using the WitMotion mobile application. The application visualizes gait parameters, enabling users to identify and understand how different footwear impacts balance, posture, and muscle activation. This portable and user-friendly device offers an accessible alternative to traditional gait analysis tools, making it suitable for individuals, clinicians, and researchers. The resulting system is a practical solution and a cost-effective innovation that bridges the gap between advanced gait analysis and real-world applications.